Sperm Donation and the Right to Privacy. Issue 2 (4th May 2017) - Hallich, Oliver
Abstract : Sperm donation is an increasingly common method of assisted reproduction. In the debate on sperm donation, the right to privacy — construed as a right that refers to the limits of the realm of information to which others have access — plays a pivotal role with regard to two questions. The first question is whether the sperm donor's right to privacy implies his right to retain his anonymity, the second is whether the gamete recipients' right to privacy entitles them to withhold information about the circumstances of their conception from their donor-conceived offspring. In this contribution, I tackle these two interrelated questions. In part (1), I defend the view that there is a prima facie right of sperm donors to remain anonymous. Part (2) widens the perspective by taking into consideration the welfare of donor-conceived offspring. I argue that anonymity may harm the child only if the gametes' recipients decide to disclose information about the circumstances of her birth to the child. Non-disclosure of these circumstances, however, is morally problematic because it may not necessarily harm, but wrong the child. In section (3), I attempt to rebut some arguments in defense of non-disclosure. In part (4), I defend the view that the best practice of sperm donation would be 'direct donation', i.e. that the identity of the donor is known from the time of conception. Part (5) concludes.